ANALISIS PERILAKU SOSIAL PESERTA DIDIK KELAS VIII DI SMP NEGERI 1 MENYUKE KABUPATEN LANDAK - Wulandara Fransisca P. Barage; Aminuyati Aminuyati; F. Y. Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research was aimed to identify the social behaviors of class VIII students of SMPN 1 Menyuke, Menyuke District of Landak Regency. This focus of this research was to find out the forms and types of social behavior of the pupils. The form of research applied was qualitative, involving class VIII A, VIII E, and one of the students (DAS) as the research subjects. The data collection tools used were observation, interviews, and documentation, while the data collection instrument used were observation guidelines, interview guidelines, and archives. The data sources of this research were three class VIII students, one social science teacher, and one class VIII E homeroom teacher. The data were analyzed through 3 phases: data reduction, data display, and conclusion drawing/verification. The findings showed that all subjects of research fall into three forms of social behavior, such as tendencies of role behaviors, social relationships, and expressive behaviors. Keywords: Social Behavior Forms, Social Behavior Types, Social Behaviors, Students, Social Science Instructions